A note on financial vulnerability and volatility in emerging stock markets: evidence from GARCH-MIDAS models. Issue 1 (2nd January 2023) - Demirer, Riza; Gupta, Rangan; Li, He; You, Yu
ABSTRACT: This paper establishes a predictive relationship between financial vulnerability and volatility in emerging stock markets. Focusing on China and India and utilizing GARCH-MIDAS models, we show that incorporating financial vulnerability can substantially improve the forecasting power of standard macroeconomic fundamentals (output growth, inflation and monetary policy interest rate) for stock market volatility. The findings have significant implications for investors to improve the accuracy of volatility forecasts.